Parenting knowledge of child development in Turkish mothers and fathers - Şenay Güven Baysal; Derya Gümüş Doğan; Sinem Kortay; Feyzullah Necati Arslan; Yeşim Demirkıran Öztürk; Fatma Hilal Yağın (Trends in Pediatrics)
Objective: Many studies have shown a positive relationship between parenting knowledge and early childhood development. We aimed to assess parenting knowledge about early childhood development and child-rearing in a sample of Turkish mothers and fathers.